2016
DOI: 10.19082/2425
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation monotherapy in transfusion-dependent beta-thalassemia major patients: a comparative study of deferasirox and deferoxamine

Abstract: IntroductionIron overload is the primary cause of mortality and morbidity in thalassemia major (TM) despite advances in chelation therapy. The aim of this study was to compare the effectiveness and safety of deferasirox (DFX) and deferoxamine (DFO) as iron-chelating agents in patients with transfusion-dependent β-thalassemia major.MethodsThis prospective randomized study included 60 patients with transfusion-dependent β-TM during the period from September 2014 to September 2015. Their ages were ≥ 6 years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Ten were multicentre trials (Calvaruso 2015; Elalfy 2015; Galanello 2006; Maggio 2009; Olivieri 1997; Pennell 2006; Pennell 2014; Taher 2017; Tanner 2007; Vichinsky 2007) and ranged from two centres in one country (Calvaruso 2015; Elalfy 2015; Olivieri 1997) to 44 centres in multiple countries (Vichinsky 2007). Six were single-centre trials (Aydinok 2007; Bahnasawy 2017; Badawy 2010; El Beshlawy 2008; Hassan 2016, Mourad 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Ten were multicentre trials (Calvaruso 2015; Elalfy 2015; Galanello 2006; Maggio 2009; Olivieri 1997; Pennell 2006; Pennell 2014; Taher 2017; Tanner 2007; Vichinsky 2007) and ranged from two centres in one country (Calvaruso 2015; Elalfy 2015; Olivieri 1997) to 44 centres in multiple countries (Vichinsky 2007). Six were single-centre trials (Aydinok 2007; Bahnasawy 2017; Badawy 2010; El Beshlawy 2008; Hassan 2016, Mourad 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Six articles reporting RCTs with a total of 1,102 included patients were eligible for inclusion in the current meta-analysis. Among them, 2 studies were from Italy [16] and Egypt [17], respectively, while the remaining 4 were multicenter trials [18-21]. The baseline characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Double-blinding was mentioned in 4 RCTs [16, 18-20], and the blinding methods used were described. Meanwhile, 2 RCTs used an open-label design [17, 21]. Incomplete outcome data were reported in 2 RCTs [19, 20], and 1 study [20] revealed a withdrawal rate of more than 20%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations